PEDAGOGICAL COMPETENCE OF INDONESIA TEACHER VIEWED FROM THE ANECDOTE WRITING LESSON PLANNING - Kumalasari, Selvia Putri; Setiawan, Budhi; Sumarlam, Sumarlam (English Department FBS UNP, 2017)
This research describes the pedagogical competence of teachers in arranging lesson plans in the 10th grade of Tour and Travel Business of SMK Negeri 6 Surakarta. The lesson plans prepared by the teachers will give impacts toward the learning practice and also the students' learning result. The approach used in this research is a qualitative approach in a descriptive research. The source of data in this research is the teachers, while the data obtained from the teachers' pedagogical competence are the readiness of the teachers to teach (RPP), sources and teaching materials. The techniques used to collect the data are interview and documentation. Based on the data analysis, the result of this research shows that the lesson plans of Bahasa Indonesia teachers in the 10th grade of Tour and Travel Business of SMK Negeri 6 Surakarta in arranging the lesson plans (RPP) is still not correspond to the component regulated in Permendikbud No. 22, 2016. However, the teachers could access their class by giving the learning method in the form of discussions. It will help the students to solve the problems which appeared in the lesson. The teachers have enclosed learning media to facilitate the students in receiving the learning material. However, the teacher still has not made the RPP in accordance with the correct components. Thus, it can be concluded that the pedagogic competence of Bahasa Indonesia teachers in the 10th grade of Tour and Travel Business of SMK Negeri 6 Surakarta is still not good, because the teacher has not made the lesson plans in accordance with components set by Permendikbud.Key words/phrases: pedagogical competence of teachers, lesson plans, writing skills, anecdote texts.KOMPETENSI PEDAGOGIK GURU BAHASA INDONESIA DITINJAU DARI PERENCANAAN PEMBELAJARAN KETERAMPILAN MENULIS ANEKDOTAbstrakPenelitian ini menggambarkan kompetensi pedagogik guru dalam menyusun perencanaan pembelajaran di kelas X Usaha Perjalanan Wisata SMK Negeri 6 Surakarta. Perencanaan pembelajaran yang disiapkan guru akan memberikan dampak pada pelaksanaan serta hasil belajar siswa. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dalam jenis penelitian deskriptif. Sumber data dalam penelitian ini adalah guru, data yang diperoleh dari kompetensi pedagogik guru adalah kesiapan guru mengajar (RPP) dan sumber serta bahan mengajar. Proses pengumpulan data dilakukan dengan teknik wawancara dan dokumentasi. Berdasarkan analisis data, hasil penelitian ini adalah perencanaan pembelajaran guru bahasa Indonesia kelas X Usaha Perjalanan Wisata SMK Negeri 6 Surakarta dalam membuat Rancangan Pelaksanaan Pembelajaran (RPP) belum sesuai dengan komponen yang di atur dalam permendikbud No 22 Tahun 2016. Namun, guru dapat mengelola kelas dengan memberikan metode pembelajaran berupa diskusi, hal ini membantu siswa dalam menyelesaikan permasalahan yang muncul dalam proses pembelajaran. Guru sudah mencantumkan media pembelajaran dalam mempermudah siswa menerima materi pelajaran. Akan tetapi guru masih belum membuat RPP sesuai dengan komponen yang benar. Dengan demikian, dapat disimpulkan bahwa kompetensi pedagogik guru bahasa Indonesia yang mengampu kelas X Usaha Perjalana Wisata SMK Negeri 6 Surakarta masih belum baik, karena guru belum membuat RPP sesuai dengan komponen yang diatur dalam permendikbud.Kata kunci/frase: kompetensi pedagogik guru, perencanaan pembelajaran, keterampilan menulis, teks anekdot